استراتجية تحسين مهارة الكلام باللغة العربية للطلاب المكثف في معهد جامعة الأمين الإسلامية برندوان سومنب مادورا - Saiful Anam; Multazam Multazam (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2022)
The purpose of this study is to understand the strategies of Al-Amien Prenduan For Islamic Studies to improve students' oral Arabic ability, as well as the supporting factors and constraints of Al-Amien Prenduan For Islamic Studies students' oral Arabic ability. This study adopts qualitative research methods and collects data in the form of interviews, observations and documents. The data analysis method used by researchers in the research is to analyze nonverbal data to verify the effectiveness of the data used by researchers. These data are undoubtedly original, and are widely used for participation, persistence, observation and triangulation. As for the results of this study, mad's strategy in improving students' Arabic speaking skills is to use writing skills to establish, provide vocabulary, update, hint or discuss, and make students understand Arabic. At a special gathering, we discussed how to improve the skills of all students at Al-Amien Prenduan For Islamic Studies. Among other students, factors that help improve Arabic students' oral skills include: the environment affects oral skills, useful numbers are hidden, punishment is frozen or punished, pure Flamingo books, behavior and language courses. Arabic competitions, such as story telling. Among other things, students are hindered in improving their oral Arabic skills: lack of enthusiasm for learning, lack of awareness, inadequate facilities and environmen.